Design of Digital Filter for Voice Noise Based on LabVIEW - WANG Kai; LV Ying-jun; QI Xue-guang (Gong-kuang zidonghua, 2011)
In view of problems of complex code program and poor portability in programming method of traditional digital filter, the paper proposed a design scheme of digital filter for voice noise based on LabVIEW. The filter uses graphical programming language LabVIEW 8.6 to realize functions of voice signal filtering, real-time measurement and storage, alarm, which has characteristics of low development fund, simple development process, convenient extend function and easy operation and usage compared with traditional filter.